contestada

Simplifying each side of the equation results in x2 − 3x − 4 = x2 − 5x + 6. Find the solution: x + 2 3x − 1 x − 2 = x − 3 3x

Respuesta :

Answer:

[tex]x=5[/tex]

Step-by-step explanation:

We have been an equation [tex]x^2-3x-4=x^2-5x+6[/tex]. We are asked to find the solution of our given equation.

[tex]x^2-x^2-3x-4=x^2-x^2-5x+6[/tex]

[tex]-3x-4=-5x+6[/tex]

Adding 5x on both sides of our equation we will get,

[tex]-3x+5x-4=-5x+5x+6[/tex]

[tex]2x-4= 6[/tex]

Upon adding 4 on both sides of our equation we will get,

[tex]2x-4+4= 6+4[/tex]

[tex]2x=10[/tex]

Now, we will divide both sides of our equation by 2.

[tex]\frac{2x}{2}=\frac{10}{2}[/tex]

[tex]x=5[/tex]

Therefore, the solution of our given equation is [tex]x=5[/tex].

The value of x from the expression is 5

Simplifying expressions

Given the equation x²-3x-4 = x²-5x+6

Collect the like terms

x² - x² -3x +5x -4 -6 = 0

Simplify the result

2x - 10 = 0

Add 10 to both sides

2x - 10 + 10 = 10

2x = 10

x = 5

Hence the value of x from the expression is 5

Learn more on expression here: https://brainly.com/question/723406

ACCESS MORE